0747 Impaired Memory Consolidation in Children with Obstructive Sleep Disordered Breathing. (27th April 2018) - Maski, K P; Steinhart, E; Holbrook, H; Kapur, K; Katz, E; Stickgold, R
Abstract: Introduction: Memory consolidation is stabilized and even enhanced by sleep (and particularly by 12–15 Hz sleep spindles in NREM stage 2 sleep) in healthy children but it is unclear what happens to these processes when sleep is disturbed by obstructive sleep disordered breathing. This cross-sectional study investigates differences in declarative memory consolidation among children with primary snoring (PS) and obstructive sleep apnea (OSA) compared to controls. We further investigate whether memory consolidation group differences are associated with NREM stage 2 (N2) sigma (12–15 Hz) spectral power band. Methods: We trained and tested participants on a spatial declarative memory task with cued recall. Retest occurred after a period of daytime wake (Wake) or a night of sleep (Sleep) with in-lab polysomnography. 36 participants ages 5–9 years completed the protocol: 14 with OSA as defined by respiratory disturbance index (RDI) > 1/hour, 12 with primary snoring (PS) and 10 controls. Results: OSA participants had poorer overall memory consolidation than controls across Wake and Sleep conditions <OSA: mean= -18.7% (5.8), controls: mean= 1.9% (7.2), t=-2.20, P=0.04>. In contrast, PS participants and controls had comparable memory consolidation across conditions. We did not detect a main effect for condition (Sleep, Wake) or group x condition interaction on memory consolidation. OSA participants had lower N2 sigma power than PS (P=0.03) and controls (P=0.004) and N2 sigma power inversely correlated with percentage of time snoring on the study night (r=-0.33, P<0.05). Further observed variable path analysis showed that N2 sigma power mediated the relationship between group and mean memory consolidation across Sleep and Wake states [ B indirect =6.76(3.5), z=2.03, P=0.04]. All results retained significance after controlling for age and BMI. Conclusion: Participants with mild OSA had impaired memory consolidation and results were mediated by N2 sigma power. These results suggest that N2 sigma power could serve as biomarker of risk for cognitive dysfunction in children with sleep disordered breathing. Support (If Any): American Sleep Medicine Foundation.